Workplace stress: implications for organizational performance in a Nigerian public university - Osibanjo, Omotayo; Salau, Odunayo P.; Falola, Hezekiah; E. Oyewunmi, Adebukola (Business: Theory and Practice, 2016)
This study investigated the implications of workplace stress on organizational performance in a Nigerian Public University. The survey method was deployed in sampling one hundred and seventy (170) staff members of the University. The Structural Equation Modelling was adopted using AMOS to establish fitness. Results of the analyses indicate that role congruence, equity, recognition, and distance, have significant influence on organizational performance. This makes it imperative for organizations to invest necessary resources in developing strategies and interventions to reduce workplace stress. If this is achieved, there will be endless opportunities in terms of increased performance and overall sustainability.